CUNANG FISH FILLETS (Muraenesox Cinerus) WITH THE APPLICATION OF GMP AND SSOP - Pola Sabar Tumohon Panjaitan; Indri yanni; Riza Rizkiah; Liliek Soeprijadi (Jurnal Perikanan Unram, 2024)
Cuckang fish (Muraenesox cinerus) are widespread in Indonesian waters, have an elongated body shape like an eel. The name of the cuckang fish (Muraensox cinerus) is different in each region, in the Pati area this fish is called "tonang" fish, while in the regions of West Kalimantan, Riau, and the Natuna Islands this fish is usually called "malong" fish. The purpose of this observation was to determine the characteristics of frozen Cangfish fillet products which were processed by applying the Good Manufacturing Process (GMP) and Standard Sanitation Operation Procedure (SSOP). It cannot be denied that fishery products or those made from fish are perishable foods. Therefore, it is necessary to make efforts to increase food safety in order to maintain and maintain the quality of frozen Cang fish fillet products for the safety of consumers.